Solutions to Increase the Efficiency of Staff Activity - GADZHIEVA, ELENA; KHORUZHY, LIUDMILA; OSIPOV, VLADIMIR; TASHTAMIROV, MAGOMED (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The main problems of the personnel component of the public civil service of the Russian Federation (transparency improvement, informatization development of processes and procedures of personnel activity, and the application of up-to-date management approaches) show the need of the state and society for a highly competitive system of the public administration as a whole. The study findings are correlated with the data from all-Russian studies which note that most people apply for public service to earn a living. Various changes in an organization, its growth, and reorganization require the adjustment of the motivation system to changing factors. RESUMEN Los principales problemas del componente personal del servicio público de la Federación Rusa (mejora de la transparencia, desarrollo de la informatización de los procesos y procedimientos de la actividad del personal, aplicación de enfoques de gestión actualizados) muestran la necesidad del Estado y la sociedad por un sistema altamente competitivo de la administración pública en su conjunto. Los hallazgos del estudio están correlacionados con los datos de toda Rusia que señalan que la mayoría de las personas solicitan el servicio público para ganarse la vida. Varios cambios en una organización, su crecimiento y reorganización requieren el ajuste del sistema de motivación a factores cambiantes.